Callous-unemotional traits, social preference and aggression among justice-involved adolescents in West Malaysia - Ng, Eng Eng (2021)
Callous-unemotional traits have been widely associated with aggression among adolescents. Researchers have also studied poor social preference leading to psychopathic traits and aggression respectively. Despite the breadth of previous findings, it is not well established as to whether the Uncaring, Callousness, and Unemotional factors of callous-unemotional traits would predict reactive aggression and proactive aggression. In addition, the role of social preference or adolescent peer likability on the interrelationships between callous-unemotional traits and aggression is unclear. As adolescents spend much of their time with their peers, finding out adolescents’ perceptions is vital.